2018
DOI: 10.1007/s12038-018-9781-2
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of microbial and associated functional diversity in the OMZ and non-OMZ areas in the Bay of Bengal

Abstract: Depletion of oxygen in certain marine areas creates oxygen minimum zones (OMZs), which can alter the species composition and abundance. We have carried out high-throughput 16S rRNA gene amplicon profiling from the Bay of Bengal (BOB) OMZ and non-OMZ areas. Typically, a total of 35 families of micro-organisms were identified as biomarkers for OMZ and non-OMZ regions in the BOB. Our analysis has identified families Pseudoalteromonadaceae, OM60 and Synechococcaceae to be abundant in oxygenated water, whereas orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 60 publications
3
21
1
Order By: Relevance
“…PICRUST analysis results obtained in the current study indicated presence of microorganisms harboring genes such as alkB, AlmA, CYP153A and AlkB are enriched in the OMZ in Arabian sea similar to the reports from Atlantic Ocean and Bay of Bengal 5153 . Presence of hydrocarbon degrading organisms points to presence of alkanes and hydrocarbon.…”
Section: Discussionsupporting
confidence: 87%
“…PICRUST analysis results obtained in the current study indicated presence of microorganisms harboring genes such as alkB, AlmA, CYP153A and AlkB are enriched in the OMZ in Arabian sea similar to the reports from Atlantic Ocean and Bay of Bengal 5153 . Presence of hydrocarbon degrading organisms points to presence of alkanes and hydrocarbon.…”
Section: Discussionsupporting
confidence: 87%
“…Also, our study has revealed the distinct bacterial diversity of Bay of Bengal when compared to OMZ regions of Peru and Chile. This work also reports the presence of bacteria involved in nitrogen metabolism [62]. Therefore, current analysis with support from the previous studies confirms the presences of nitrate reducing cultivable bacteria in BOB and Arabian Sea areas.…”
Section: Enzyme Assayssupporting
confidence: 89%
“…Large amounts of particulate and dissolved organic matter are characteristic of the watercourses flowing into the Bay of Bengal. Gammaproteobacteria and Alphaproteobacteria dominated the bacterial community composition of the waters of the Bay of Bengal (Ghosh and Bhadury, 2018;Rajpathak et al, 2018;Fernandes et al, 2019;Dhal et al, 2020) and these classes together with Deltaproteobacteria were detected abundantly in sediments of the Sundarbans (Basak et al, 2015). In this study, Deltaproteobacteria were mainly represented by Geobacter at K8 with relevance for the arsenic cycle (Gnanaprakasam et al, 2017).…”
Section: Bacterial Community Composition and Potential Roles Across Tmentioning
confidence: 48%